Hazard Identification, Risk Assessment, and Determining Control (HIRADC) Method in a University Laboratory in Surabaya, Indonesia - Rika Fauziah1, Putri Ayuni Alayyannur1, Dani Nasirul Haqi1, Sho’im Hidayat1, Alfin Wahyudiono F1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Risk management is a system owned by every organization, including university laboratory, to prevent losses. Amongst the methods of risk management that are usually applied is HIRADC method, which is a systematic stage to identify hazards, to assess and analyze risks, and to plan controls measures according to the existed risks. This research is observational research which aims to describe the phenomena. There are several stages in this method, namely hazard identification, risk analysis, and determining control. The data is collected by conducting observation before doing data matching with laboratory worker. The research results indicate that from five activities performed in the Laboratory of Histology Anatomy at Faculty of Medicine Universitas Airlangga, such as experiments by the medical students, dry cadaver shaping, new cadaver shaping, cadaver maintenance and the goods burning by the laboratory worker, there are 16 hazards discovered, with two extreme-risk hazards and three high-risk hazards. The controls and recommendation provided are giving socialization about the importance of wearing PPE (rubber gloves, safety goggles, and laboratory coat), providing explanation about the work to the worker as well as explanation about the laboratory SOP and providing the fire extinguishers